RUSSIAN COLONIAL POLICY IN TURKESTAN - ESTABLISHMENT OF A CENTRALIZED ADMINISTRATIVE SYSTEM - Valieva Nafisa Abdumajitovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the consequences of the establishment of a centralized management system in Turkestan, as well as the issues of military, household trade, post, telegraph, and railway management, which are part of the country’s commissariat and play a key role in management, were completely left to the discretion of the relevant agencies in Russia, as a result of which Turkestan became the executive body of the CIS. will be illuminated.